In Silico Investigation of the Neurotensin Receptor 1 Binding Site: Overlapping Binding Modes for Small Molecule Antagonists and the Endogenous Peptide Agonist. Issue 1 (16th September 2015) - Lückmann, Michael; Holst, Birgitte; Schwartz, Thue W.; Frimurer, Thomas M.
Abstract: The neurotensin receptor 1 (NTSR1) belongs to the family of 7TM, G protein‐coupled receptors, and is activated by the 13‐amino‐acid peptide neurotensin (NTS) that has been shown to play important roles in neurological disorders and the promotion of cancer cells. Recently, a high‐resolution x‐ray crystal structure of NTSR1 in complex with NTS8–13 has been determined, providing novel insights into peptide ligand recognition by 7TM receptors. SR48692, a potent and selective small molecule antagonist has previously been used extensively as a tool compound to study NTSR1 receptor signaling properties. To investigate the binding mode of SR48692 and other small molecule compounds to NTSR1, we applied an Automated Ligand‐guided Backbone Ensemble Receptor Optimization protocol (ALiBERO), taking receptor flexibility and ligand knowledge into account. Structurally overlapping binding poses for SR48692 and NTS8–13 were observed, despite their distinct chemical nature and inverse pharmacological profiles. The optimized models showed significantly improved ligand recognition in a large‐scale virtual screening assessment compared to the crystal structure. Our models provide new insights into small molecule ligand binding to NTSR1 and could facilitate the structure‐based design of non‐peptide ligands for the evaluation of the pharmacological potential of NTSR1 in neurological disorders and cancer. Abstract :